2021
DOI: 10.3892/etm.2021.10390
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 facilitates the invasion and metastasis of non‑small cell lung cancer cells through regulating VEGF, EMT and the Notch1/Hes1 pathway

Abstract: Forkhead box P3 (FOXP3) is a specific marker of regulatory T cells (Tregs) that is also expressed in tumour cells. Previous studies have revealed that FOXP3 can promote metastasis in several types of cancer, including non-small cell lung cancer (NSCLC); however, the underlying mechanism of FOXP3 remains unclear. The aim of the present study was to investigate the effect of FOXP3 on vascular endothelial growth factor (VEGF), epithelial-to-mesenchymal transition (EMT) and the Notch1/Hes1 pathway in NSCLC. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Interestingly, HES1, associated with Notch activation, was essential to inhibit the progression of B-cell acute lymphoblastic leukemia rather than T-cell acute lymphoblastic leukemia ( 47 ). Besides, HES1 has been shown to be positively correlated with the expression of FOXP3 and plays an important role in regulating the invasive and migratory functions of FOXP3 in NSCLC cells ( 48 ). ITM2C belongs to the Type II Integral Membrane protein (ITM2) family and is thought to be negatively regulates the amyloid-beta peptide production ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HES1, associated with Notch activation, was essential to inhibit the progression of B-cell acute lymphoblastic leukemia rather than T-cell acute lymphoblastic leukemia ( 47 ). Besides, HES1 has been shown to be positively correlated with the expression of FOXP3 and plays an important role in regulating the invasive and migratory functions of FOXP3 in NSCLC cells ( 48 ). ITM2C belongs to the Type II Integral Membrane protein (ITM2) family and is thought to be negatively regulates the amyloid-beta peptide production ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CTLA4 interacts with PKCη through CTLA4/PKCη/GIT/PAK/PIX signaling pathway in Tregs, which leads to depletion of the costimulatory molecule CD86 on intratumoral CD103+ DCs, inactivation of CD8+ T cells, and inhibition of effector cytokines production by these cells [38]. Furthermore, FOXP3 suppression can inhibit tumor invasion and metastasis via downregulating the angiogenic factor VEGF, the epithelial-mesenchymal transition (EMT), and the Notch1/Hes1 pathway [39]. Additionally, FOXP3 was reported to promote cell proliferation, invasion and EMT through activation of the Wnt signaling pathway, and consequently upregulation of β-catenin and transcription factor 4 (TCF4) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FOXP3 is overexpressed to facilitate the invasion and metastasis of NSCLC (Li et al, 2021). Our results showed there were different expression levels of the FOXP family according to different pathological types in NSCLC compared with normal tissue.…”
Section: Discussionmentioning
confidence: 45%